2006
DOI: 10.1210/en.2005-1275
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Recent Progress in Gonadotropin-Releasing Hormone Neuronal Migration

Abstract: Neurons that synthesize GnRH are critical brain regulators of the reproductive axis, yet they originate outside the brain and must migrate over long distances and varied environments to get to their appropriate positions during development. Many studies, past and present, are providing clues for the types of molecules encountered and movements expected along the migratory route. Recent studies provide real-time views of the behavior of GnRH neurons in the context of in vitro preparations that model those in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 89 publications
4
96
0
2
Order By: Relevance
“…Previous studies have already described the axophilic migration of GnRH neurons in the forebrain (Yoshida et al, 1995;Murakami et al, 2000). In mice, peripherin-positive fibers belonging to the caudal branch of the vomeronasal nerve (cVNN) are shown to take a characteristic turn ventrally into the basal forebrain, suggesting the migration of GnRH neuron to be axophilic in nature (Tobet and Schwarting, 2006). In the present study we identified another mode of migration at the most caudal level of the axophilic migratory pathway.…”
Section: Ventral-directed Migration Of Gnrh Neuronssupporting
confidence: 62%
“…Previous studies have already described the axophilic migration of GnRH neurons in the forebrain (Yoshida et al, 1995;Murakami et al, 2000). In mice, peripherin-positive fibers belonging to the caudal branch of the vomeronasal nerve (cVNN) are shown to take a characteristic turn ventrally into the basal forebrain, suggesting the migration of GnRH neuron to be axophilic in nature (Tobet and Schwarting, 2006). In the present study we identified another mode of migration at the most caudal level of the axophilic migratory pathway.…”
Section: Ventral-directed Migration Of Gnrh Neuronssupporting
confidence: 62%
“…Although the mechanisms regulating the initial stages of GnRH neuron migration out of the nasal compartment and into the basal forebrain are becoming clear (for reviews, see Wray, 2002;Tobet and Schwarting, 2006;Cariboni et al, 2007), there is little information regarding the mechanisms that regulate cessation of migration, or positioning of cells within the basal forebrain.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH gene expression commences at E11.5 (Schwanzel-Fukuda and Pfaff, 1989), and so serves as a reliable marker for monitoring GnRH neurons from early differentiation to adulthood. Time series in situ hybridization and immunohistochemistry experiments examining GnRH gene or protein expression, respectively, have been performed to monitor the progress of GnRH neuron migration out of the nasal region and into the brain, and, coupled with analysis of migration defect mutants, a clear picture of this process is now forming (for reviews, see Wray, 2002;Tobet and Schwarting, 2006;Cariboni et al, 2007). Despite extensive investigation into understanding the cellular and molecular underpinnings of GnRH neuron migration, particularly at the early stages, the relationship between time of differentiation and the final anatomical position of individual GnRH neurons is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the establishment of the migration route and the movement of GnRH neurons are thought to involve different classes of molecules (for review, see Tobet and Schwarting, 2006). Candidates include semaphorins and their receptors, because of their high levels of expression in the developing olfactory system (Wray, 2001).…”
Section: Introductionmentioning
confidence: 99%